Evidence for periodic variations in the thickness of Saturn's nightside plasma sheet. Issue 1 (19th January 2017) - Thomsen, M. F.; Jackman, C. M.; Cowley, S. W. H.; Jia, X.; Kivelson, M. G.; Provan, G.
Abstract: During certain portions of the Cassini mission to Saturn, Cassini made repeated and periodic crossings of the magnetospheric current sheet that lies near the magnetic equator and extends well down the magnetospheric tail. These repeated crossings are part of the puzzling set of planetary period variations in numerous magnetospheric properties that have been discovered at Saturn. During 2010 these periodic crossings often display asymmetries such that the northbound crossing occurs faster than the southbound crossing or vice versa, while at other times the crossings are more symmetric. The character of the crossings is well organized by the relative phase of the northern versus southern perturbation currents inferred in earlier analyses of the magnetic field observations. Further, the dependence of the character of the crossings on the relative phase is consistent with similar asymmetries predicted both by the dual rotating current systems inferred from magnetic field observations and by global MHD models that incorporate the effects of hypothesized atmospheric vortices. The two models are themselves in generally good agreement on those predictions. In both models the asymmetries are attributable to a periodic thickening and thinning of the magnetospheric current sheet, combined with a periodic vertical flapping of the sheet. The Cassini observations thus provide additional observational support to such current systems as a likely explanation for many of the known magnetospheric planetary period variations. Plain Language Summary: During certain intervals when Cassini's orbit takes it into Saturn's magnetic tail, it periodically crosses the thin current sheet that separates the northern and southern magnetic lobes of the tail. These periodic crossings (north‐to‐south and south‐to‐north) occur approximately at the planet's rotational period and are part of the puzzling set of planetary period variations in numerous magnetospheric properties that have been discovered at Saturn. We find that sometimes the northbound crossing appears to occur faster than the southbound crossing and at other times the reverse is true, while at still other times the crossings are more symmetric. The observed asymmetries are consistent with a periodic thickening and thinning of the magnetospheric current sheet as expected by two theoretical models, which invoke strong field‐aligned current systems driven by two flow vortices in Saturn's northern and southern atmospheres. These observations thus supplement other observational support that these current systems are a likely explanation for many of the known magnetospheric planetary period variations. Key Points: Periodic crossings of Saturn's tail current sheet often are asymmetric such that northbound crossings are faster or slower than southbound Character of crossings depends on relative phase of the northern versus southern perturbation currents previously derived from magnetic data Observed asymmetries are consistent with a periodically variable thickness of the magnetospheric current sheet, as theoretically expected